"Lights and Sirens": Variation in 911 Call‐Taker Risk Appraisal and its Effects on Police Officer Perceptions at the Scene. (22nd December 2021) - Gillooly, Jessica W.
Abstract: Until now, 911 dispatch centers largely have been the "black box" of the criminal justice system. This article opens that black box. It documents systematically a new mechanism in the policing process: the degree to which a 911 call‐taker's "alarmist" response to a call primes police officer perceptions at the scene. This study leverages the quasi‐random assignment of 911 call‐takers to calls and employs an instrumental variable approach novel to dispatch. The author focuses her analysis on call‐for‐service data (N = 20, 764) involving mental health crises and public assaults—strategic sites for the investigation of call‐taker discretion—from a dispatch center in Southeast Michigan and finds a statistically significant difference in the propensity of call‐takers to classify the same types of calls as "high priority." This variation, in turn, affects police perceptions. Calls for which call‐taker assignment induces a high priority classification are about three times more likely to be classified as high priority by the police at the scene, relative to the mean of the dependent variable. Effects are strongest for calls involving mental health crises. The theoretical developments and empirical results presented here point to new areas for policy reform for policymakers and practitioners regarding the importance of training 911 call‐takers in call triage and diversion.